Potential of Vegetable E-Commerce for Empowering Farmers in Indonesia - Atika Dian Pitaloka; Hartoyo Hartoyo; Mochammad Mukti Ali (Universitas Islam Negeri Walisongo Semarang, 2021)
The Covid-19 pandemic has disrupted the flow of horticultural products from farmers to consumers. It causes the delivery of vegetables to be hampered, especially in Jabodetabek, which is the center of vegetable consumption. Therefore, a new marketing strategy is needed involving e-commerce to meet people's need for vegetables. This study discusses the buying behavior of vegetables through e-commerce in Jabodetabek and analyzes the role of e-commerce platforms to empower farmers in Indonesia. The method used in this research is descriptive qualitative with two data sources, primary data obtained from questionnaires filled out by 153 respondents and secondary data obtained from literature studies. The results showed that 50.33 percent of respondents prefer to shop for vegetables through e-commerce, and 51.63 percent think online vegetable shopping services are better than offline or conventional shopping. The majority of people choose to buy vegetables online through e-commerce because of concerns about the spread of the COVID-19 virus. However, vegetable purchasing behavior is still in the introduction stage. E-commerce plays a role in making it easier for people to get the needs of quality vegetables at competitive prices. Empowering farmers to produce high-quality products is very important in increasing consumer repurchase intentions and improving the welfare of farmers in Indonesia.